Functional Characterization of Lamina X Neurons in ex-Vivo Spinal Cord Preparation - Krotov, Volodymyr; Tokhtamysh, Anastasia; Kopach, Olga; Dromaretsky, Andrew; Sheremet, Yevhenii; Belan, Pavel; Voitenko, Nana (Frontiers in Cellular Neuroscience, 2017)
Functional properties of lamina X neurons in the spinal cord remain unknown despite the established role of this area for somatosensory integration, visceral nociception, autonomic regulation, and motoneuron output modulation. Investigations of neuronal functioning in the lamina X have been hampered by technical challenges. Here we introduce an ex-vivo spinal cord preparation with both dorsal and ventral roots still attached for functional studies of the lamina X neurons and their connectivity using an oblique LED illumination for resolved visualization of lamina X neurons in a thick tissue. With the elaborated approach, we demonstrate electrophysiological characteristics of lamina X neurons by their membrane properties, firing pattern discharge and fiber innervation (either afferent or efferent). The tissue preparation has been also probed using Ca2+ imaging with fluorescent Ca2+ dyes (membrane-impermeable or -permeable) to demonstrate the depolarization-induced changes in intracellular calcium concentration in lamina X neurons. Finally, we performed visualization of subpopulations of lamina X neurons stained by retrograde labeling with aminostilbamidine dye to identify sympathetic preganglionic and projection neurons in the lamina X. Thus, the elaborated approach provides a reliable tool for investigation of functional properties and connectivity in specific neuronal subpopulations, boosting research of lamina X of the spinal cord.